Development of Interactive Media Using Macromedia Flash 8 Software in Natural Sciences Subjects in Elementary Schools - Rahma Taher; Alwen Bentri (STAI Hubbulwathan Duri, 2024)
This research aims to develop interactive media using Macromedia Flash 8 software in science and technology subjects in elementary schools. This research uses a Research and Development (RD) approach with the Analysis, Design, Develop, Implement, Evaluate (ADDIE) model. It was conducted at three elementary schools in West Sumatra with fourth-grade students as research subjects. Qualitative and quantitative data were obtained from teacher and student practicality questionnaires, as well as evaluation tests in the form of pretest and posttest. Data collection utilized validation sheets, questionnaires, and evaluation tests. The results of the interactive multimedia validity test based on Macromedia Flash 8 were found to be in a very valid category (scoring 81-100% based on expert assessments) with an average percentage of 90%. The practicality assessment yielded an average percentage of 88.5% in the highly practical category (scoring 85.01-100%). The effectiveness evaluation resulted in an N-Gain Score (a metric measuring the increase between pre and post-test scores) of 0.77, indicating a high level of gain, and a percentage of 77.87 in the effective category.The evaluations affirm that Macromedia Flash 8-based interactive media is valid, practical, effective, and suitable for educational use in enhancing science learning for elementary students. The findings have implications for integrating such multimedia tools in science curriculum design and teacher training to facilitate more engaging and effective delivery of abstract scientific concepts. Future research could explore wider implementation and long-term impacts on student learning outcomes.